Crystal Structure Analysis of Wild Type and Fast Hydrolyzing Mutant of EhRabX3, a Tandem Ras Superfamily GTPase from Entamoeba histolytica. Issue 1 (16th January 2016) - Srivastava, Vijay kumar; Chandra, Mintu; Saito-Nakano, Yumiko; Nozaki, Tomoyoshi; Datta, Sunando
Abstract: The enteric protozoan parasite, Entamoeba histolytica, is the causative agent of amoebic dysentery, liver abscess and colitis in human. Vesicular trafficking plays a key role in the survival and virulence of the protozoan and is regulated by various Rab GTPases. Eh RabX3 is a catalytically inefficient amoebic Rab protein, which is unique among the eukaryotic Ras superfamily by virtue of its tandem domain organization. Here, we report the crystal structures of GDP-bound fast hydrolyzing mutant (V71A/K73Q) and GTP-bound wild type Eh RabX3 at 3.1 and 2.8 Å resolutions, respectively. Though both G-domains possess "phosphate binding loop containing nucleoside triphosphate hydrolases fold", only the N-terminal domain binds to guanine nucleotide. The relative orientation of the N-terminal domain and C-terminal domain is stabilized by numerous inter-domain interactions. Compared to other Ras superfamily members, both the GTPase domains displayed large deviation in switch II perhaps due to non-conservative substitutions in this region. As a result, entire switch II is restructured and moved away from the nucleotide binding pocket, providing a rationale for the diminished GTPase activity of Eh RabX3. The N-terminal GTPase domain possesses unusually large number of cysteine residues. X-ray crystal structure of the fast hydrolyzing mutant of Eh RabX3 revealed that C39 and C163 formed an intra-molecular disulfide bond. Subsequent mutational and biochemical studies suggest that C39 and C163 are critical for maintaining the structural integrity and function of Eh RabX3. Structure-guided functional investigation of cysteine mutants could provide the physiological implications of the disulfide bond and could allow us to design potential inhibitors for the better treatment of intestinal amebiasis. Graphical abstract: Highlights: Eh RabX3 is an atypical amoebic Rab GTPase with tandem G-domains and exhibit a very low catalytic efficiency. Crystal structure of Eh RabX3 reveals the relative orientation of N- and C-terminal G-domains that are constrained by a short linker. The inter-domain interface is stabilized by both polar and non-polar interactions. Although both the domains exhibited same overall fold, only the N-terminal one showed nucleotide bound to its active site. The nucleotide-bound N-terminal domain shows significant deviation in its functional motifs from the Ras superfamily members. Due to non-conservative substitutions (V71 and K73) in the switch II region, the complete segment changes its conformation and moved away from the active site. The crystal structure of V71A/K73Q provides a possible explanation for the low catalytic efficiency of Eh RabX3. The crystal structure and further biochemical analysis reveals the existence of an intra-molecular disulfide bond that is critical for maintaining the structural integrity and function of Eh RabX3. Disrupting the intra-molecular disulfide bridge in Eh RabX3 renders the protein unstable, which could be used as an important tool for deciphering the biological function of this protein in amoebic trophozoites.